Penerapan Metode Fuzzy Multi Criteria Decision Making Pada Interpretasi Hasil Penentuan Kemiskinan Provinsi Jawa Timur - Diya, Hakimatul Maulidiyah; Turmudi, Turmudi (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
Fuzzy Multi Criteria Decision Making (FMCDM) method is a method of making decisions based on certain criteria to determine the best alternative among several alternatives. The purpose of the FMCDM method is to obtain the best alternative that is accurate and optimal. Poverty is a condition in which economic needs are not met against the average standard of living in the region. Poverty is a very important issue for the government or related agencies. This problem can be solved by determining the district/city area which is included in the poor category. So a method is needed that can be used to determine the existence of poverty in an area. The solution to overcome this problem is to use the FMCDM method. The solution to overcome this problem is to use the FMCDM method. The FMCDM process begins by determining objectives, alternative decisions, and a collection of criteria that will be used to determine poor districts/cities in East Java Province. The alternative decisions consist of 38 regencies/cities of East Java Province, while the set of criteria consists of the Percentage of Poor People, Human Development Index, Poverty Depth Index, and Poverty Severity Index. The next step evaluates the fuzzy set by aggregating the weight of the criteria and the degree of fit of each alternative to its criteria. The aggregation result is called the fuzzy match index which consists of three values, namely, the value which represents the result of the lower limit aggregation, the value which represents the middle bound, and the value which represents the upper bound value. The three values are ranked using the ranking method for fuzzy numbers with degrees of optimasan. So that the total integral value for each alternative will be a decision from the highest priority to the lowest in determining the districts / cities included in the poor category and as an effort to reduce poverty in East Java Province.